Structural and pain modifications in models of osteoarthritis - Nwosu, Lilian Ngozi (2015)
Background: Despite the extensive research into the pathophysiology of osteoarthritis (OA), pain still represents a significant unmet clinical need. This thesis explores the effects of a tropomyosin related kinase A receptor (TrkA) inhibitor and an anti-nerve growth factor (NGF) antibody as interventions to modify inflammation, structural pathology and pain behaviour in rat models of OA.